1984
DOI: 10.1128/jcm.20.4.618-623.1984
|View full text |Cite
|
Sign up to set email alerts
|

Clinical laboratory comparison of the 10-ml isolator blood culture system with BACTEC radiometric blood culture media

Abstract: The efficiency of the 10-ml Isolator (E. I. du Pont de Nemours & Co., Inc.) for recovery of pathogens from blood was compared with that of BACTEC 6B and 7C media (Johnston Laboratories) by using 4,195 cultures from 1,662 patients. During the first phase of the study, BACTEC bottles were inoculated with 3 ml of blood; in the second phase, bottles were inoculated with 5 ml. The objectives were to compare results with similar blood volumes used for the detection of anaerobes as well as similar overall volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
18
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 16 publications
5
18
0
Order By: Relevance
“…Most studies report between 1 and 100 CFU/mL (20). However, some have documented concentrations of < 1 CFU/mL (21)(22)(23) and some > 100 CFU/mL (24,25). Although the present assay has good sensitivity, it is not adequate to detect most bacteremias.…”
Section: Discussionmentioning
confidence: 75%
“…Most studies report between 1 and 100 CFU/mL (20). However, some have documented concentrations of < 1 CFU/mL (21)(22)(23) and some > 100 CFU/mL (24,25). Although the present assay has good sensitivity, it is not adequate to detect most bacteremias.…”
Section: Discussionmentioning
confidence: 75%
“…du Pont de Nemours & Co., Inc., Wilmington, Del.) technique has been studied extensively (1,3,4,9,11,12,(16)(17)(18)(19)29), and several authors report that LC may be advantageous for detecting organisms in the presence of antibiotics (12,16,23,29). The LC technique, however, requires centrifugation and manipulation, which cannot always be promptly performed in laboratories with limited staffing.…”
mentioning
confidence: 99%
“…While most studies on the Isolator (E. I. du Pont de Nemours & Co., Inc., Wilmington, Del.) report that it enables the recovery of significantly more bacteria and fungi from the blood than do conventional bottle systems, the lysis-centrifugation device nevertheless failed to detect from 9 to 29% of the pathogens in these studies (1, 2, 4-6, [8][9][10][11][12]. One of the assets of the Isolator is the frequency with which it detects very small numbers of pathogens which may be missed by bottle systems.…”
mentioning
confidence: 99%
“…One of the assets of the Isolator is the frequency with which it detects very small numbers of pathogens which may be missed by bottle systems. In one study (9), 50% of the pathogens recovered by the Isolator yielded a total of 10 colonies or less from 10 ml of blood; 18% were recovered as a single colony. Kiehn et al (11) similarly reported that 52% of their positive Isolator cultures contained less than 1 CFU/ml of blood.…”
mentioning
confidence: 99%
See 1 more Smart Citation